Parâmetros curriculares nacionais em escolas da rede privada de ensino da cidade de São Paulo: um estudo exploratório - Nastri, Ivete (2008)
The present study lies in the construction of Curriculum, highlighting the debate on the National Curriculum Parameters trajectory in private schools, focusing on the perception and the receptivity of this proposal, seeking after an answer if, in fact, the adoption of a National Curriculum interfered with the changes in educators pedagogical practice. To achieve its objective, this study s methodological procedure is based on a qualitative approach, contemplating the analytical descriptive focus and prioritizing the analysis of the answers given to the questionnaires and the informal conversations observed in the speech of educators from five private schools studied in the capital of São Paulo. The results figure in this study as follows: a) Introduction, b) Curriculum Policies in the 90s, where the historical context in which the National Curriculum was created is examined, and National Curriculum Parameters, where the proposal of a national curriculum and the attitude of educators, class entities and politicians to the official document are presented, c) Method, d) Presentation and discussion of results in which both the educator s profile and the official curriculum trajectory in private schools figure, from the analysis of principals , coordinators and teachers speech - the ones who play a leading role in the whole process, and e) Concluding Remarks, where the possibilities and limits of the official curriculum as a curricular policy are discussed